Tenfold increase in the fusion triple product caused by doubling of toroidal magnetic field in the spherical tokamak Globus-M2. (20th April 2021) - Kurskiev, G.S.; Gusev, V.K.; Sakharov, N.V.; Balachenkov, I.M.; Bakharev, N.N.; Bulanin, V.V.; Chernyshev, F.V.; Kavin, A.A.; Kiselev, E.O.; Khromov, N.A.; Minaev, V.B.; Miroshnikov, I.V.; et al.
Abstract: The current work reports on the significant rise of the fusion triple product in experiments carried out on the compact spherical tokamak (ST) Globus-M2 with a twofold increase in the toroidal magnetic field. A tenfold rise in the n . T . τ E product was recorded during an increase in the magnetic field from 0.4 to 0.8 T and the plasma current from 0.25 to 0.4 MA at an unchanged auxiliary heating power value. Limited reasons may affect this positive trend, among which are energy confinement improvement and an increase in the efficiency of neutral beam heating. Despite the increase in the magnetic field, the neutral beam injection (NBI) led to clear and reproducible transition to the H-mode accompanied by a decrease in the turbulence level at the plasma edge. It was experimentally confirmed that strong dependence of the energy confinement time on the magnetic field value is conserved at a higher magnetic field approaching 0.8 T. Enhancement of energy confinement is connected to a collisionality ( ν * ) decrease. While for conventional tokamaks the confinement dependence on collisionality becomes weaker with decreasing ν * dependence, in the ST, in contrast, we observe its strengthening.